Answer:
Step-by-step explanation:
just simplify the LHS first.
You can either multiply 1/5 by (x+3) and then solve
or
multiply both sides by 5 to get rid of 1/5 on LHS
I will multiply by 5
(x+3)= -10x-15 ( 5*1/5(x+3)= -5(2x+3)
now rearrange the equation
x+3=-10x-15
-10x-15-x-3=0
-11x-17=0
-11x=17
x= -17/11
Answer:
10
Step-by-step explanation:
f(-3)=-2(-3)+4=6+4=10
So 1 would be 5r+20 and then the second one would be
Answer:
x=11
Step-by-step explanation:
You do 38/3x+3 and 19/x+7 and then cross mulitply and get 57x+57=38x+266. Then yoy subtract 57 from 266 and get 57x=38x+209. Now you have to subtract 38 from 57 and then answer will be 19. So now you have 19x=209. Finally you divide 209 by 19 and get x=11. Good luck!